A positive electrode material and a preparation method thereof and a battery
By using a polyaniline coating layer and a CeO2 dispersion layer on the positive electrode material, the problems of structure collapse, poor air stability and water absorption after the increase in the charge and discharge times of the positive electrode material are solved, and its magnification and circulation performance are significantly improved.
Patent Information
- Application Number
- CN202211453335.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-11-21
AI Technical Summary
The existing sodium-ion battery and lithium-ion battery positive electrode materials are prone to structural collapse, poor air stability and easy water absorption after the increase in the number of charge and discharge, resulting in a degradation of circulation and rate performance.
A polyaniline coating layer, including a polyaniline matrix and CeO2 dispersed therein, is coated on the surface of the positive electrode active material to improve its stability in air and compatibility with the electrolyte while enhancing the conductivity and thermal stability of the positive electrode material.
The rate performance and circulation performance of the positive electrode material are improved, the reaction between moisture and electrolyte salt is avoided, the corrosion and impedance of the positive electrode active substance is reduced, and the overall performance of the battery is improved.
Smart Images

Figure CN115763738B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a positive electrode material and a preparation method thereof and a battery. Background Art
[0002] As lithium-ion batteries are widely used in the field of electric vehicles, the demand for lithium resources has greatly increased. However, the reserves of lithium in the earth's crust are only 0.0017%, and there is still no effective lithium resource recovery technology, which obviously cannot meet the growing needs of large-scale energy storage and electric vehicles. The reserves of sodium in the earth's crust are much higher than those of lithium, and sodium has the advantages of wide distribution and low cost. At the same time, sodium and lithium belong to the same main group elements and exhibit similar "rocking chair" electrochemical charging and discharging behaviors in battery operation.
[0003] At present, common positive electrode materials for sodium ion batteries mainly include layered transition metal oxides, Prussian blue analogs and polyanion compounds. Compared with Prussian blue analogs and polyanion compound materials, layered transition metal oxides show higher specific capacity and better meet the needs of high energy density. However, as the number of charge and discharge times of this type of material increases, the trivalent manganese ions will produce the Jahn Teller effect, resulting in lattice distortion and structural destruction, and the larger sodium ions will cause structural collapse during the extraction and embedding process, which seriously affects the battery's cycle performance and rate performance, causing the electrochemical performance to decay more and more seriously. At the same time, the transition metal layered oxide positive electrode material of sodium ion batteries has poor air stability, and the surface easily absorbs water, resulting in an increase in moisture. When assembled into a battery, the residual moisture in the positive electrode material will react with the salt in the electrolyte to generate HF, and a vicious cycle reaction will occur, reducing the battery's cycle performance.
[0004] The problems of structural collapse, poor air stability and easy water absorption are not only found in sodium ion battery positive electrode materials, but also in lithium ion battery positive electrode materials, which will also affect the cycle performance and rate performance of lithium ion battery positive electrode materials. At present, the common methods for modifying positive electrode materials include coating and doping. For example, CN115159593A discloses a precursor material and a preparation method thereof and a positive electrode material with element doping and cobalt in-situ coating. The chemical formula of the precursor material is Ni x Co y Mn z M p(OH)2@Co(OH)2, wherein 0.7≤x<1, 0≤y≤0.2, 0<z≤0.3, x+y+z+p=1, M is a doping element, and the doping element in the precursor material is distributed in a "low concentration-high concentration-low concentration-high concentration-low concentration" cycle from the inside to the outside, and cobalt is deposited on the surface of the precursor by a coprecipitation process to form a cobalt coating layer. The positive electrode material prepared using the precursor material has good cycle performance. For example, CN115207325A discloses a coated sodium ion battery positive electrode material, which includes at least one formula of Na p Ni x Mn y M 1-x-y O 2-z F z and at least one compound coated with Na p Ni x Mn y M 1-x-y O 2- z F z The lithium-containing compound on the surface of the compound, wherein M is a doping element, and the mass proportion of the lithium-containing compound is 0.02% to 2.0%, which effectively solves the problem that the positive electrode material of the sodium ion battery is easily affected by moisture in the air, resulting in deterioration of the electrical performance. For example, CN115148970A discloses an olivine NaMPO4-coated high-nickel ternary or lithium-rich manganese-based positive electrode material and a preparation method thereof, wherein the NaMPO4-coated high-nickel ternary or lithium-rich manganese-based positive electrode material is a NaMPO4 (M = Ni, Co, Mn) surface-modified layered high-nickel ternary positive electrode material or lithium-rich manganese-based positive electrode material, and the NaMPO4 coating layer can fundamentally inhibit the precipitation of lattice oxygen and improve the structural stability of high-nickel ternary and lithium-rich manganese-based positive electrode materials.
[0005] However, the above-mentioned method of modifying the positive electrode material is only limited to improving the structural stability and cycle performance of the positive electrode material, and cannot improve its rate performance. Therefore, preparing a positive electrode material with both good cycle performance and good rate performance is an urgent problem to be solved. Summary of the invention
[0006] In view of the above problems existing in the prior art, the object of the present invention is to provide a positive electrode material and a preparation method thereof and a battery.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a positive electrode material, comprising a positive electrode active substance and a polyaniline coating layer located on the surface of the positive electrode active substance, wherein the polyaniline coating layer comprises a polyaniline matrix and CeO2 dispersed in the polyaniline matrix.
[0009] The surface of the positive electrode material of the present invention is coated with a polyaniline coating layer. Polyaniline is a good conductive polymer. The hydrogen bonds in the polyaniline structure can be electrostatically adsorbed with the positive electrode active material, so that it can be evenly coated on the surface of the positive electrode active material. The coating layer makes up for the shortcomings of the positive electrode active material being sensitive to moisture and carbon dioxide in the air, and can improve the stability of the positive electrode active material in the air, thereby avoiding the occurrence of gel and agglomeration in the process of preparing the positive electrode slurry, and avoiding the reaction of residual moisture and salt in the electrolyte during the cycle of the battery. In addition, the polyaniline coating layer has good compatibility with the electrolyte, and can avoid contact between the electrolyte and the positive electrode active material, thereby inhibiting the side reaction between the electrolyte and the positive electrode active material, reducing the corrosion degree of the surface of the positive electrode active material and reducing the impedance of the positive electrode active material. At the same time, CeO2 is dispersed in the polyaniline coating layer, which increases the electronic and ionic conductivity of the positive electrode material and improves the comprehensive conductivity of the positive electrode material. In addition, CeO2 also enhances the structural stability of the polyaniline coating layer and the thermal stability of the positive electrode material. At the same time, the coating layer has a larger specific surface area and more molecular channels, thereby ensuring a larger contact area between the positive electrode material and the electrolyte while providing more active points for the electrochemical reaction, which is conducive to the embedding and extraction of ions. The above factors work together to improve the rate performance and cycle performance of the positive electrode material.
[0010] Preferably, based on the mass of the positive electrode material as 100wt%, the content of the polyaniline coating layer is 0.1-10wt%, for example, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.
[0011] In the present invention, too much polyaniline content in the polyaniline coating layer of the positive electrode material will result in a thicker coating layer on the surface of the positive electrode active material, which increases the transmission distance of ions, makes it difficult for ions to be removed and embedded, increases impedance, and reduces the capacity and first coulomb efficiency and cycle performance of the material. Too little polyaniline content in the polyaniline coating layer will result in a thinner coating layer on the surface of the positive electrode active material, resulting in too low a coating rate of the positive electrode material, which is easy to react with the salt in the electrolyte, causing the dissolution of metal ions and reducing the rate and cycle performance of the material.
[0012] Preferably, the molecular weight of the polyaniline in the polyaniline coating layer is 1000-10000, for example, 1000, 5000 or 10000.
[0013] The molecular weight of the polyaniline in the polyaniline coating layer of the present invention is preferably within the above range. The polyaniline within this range has good solubility in the solvent. The positive electrode active material is placed in a solvent in which the polyaniline with the above molecular weight is dissolved, and a uniform polyaniline coating layer is formed on the surface of the positive electrode active material through electrostatic adsorption, thereby avoiding the difficulty of ion escape and embedding caused by the coating layer being too thick.
[0014] Preferably, the polyaniline in the polyaniline coating layer is organic protonic acid-doped polyaniline.
[0015] Compared with undoped polyaniline, organic acid-doped polyaniline can further improve the electronic conductivity of polyaniline and improve the solubility of polyaniline.
[0016] Preferably, the organic protonic acid includes at least one of methanesulfonic acid, dodecylsulfonic acid, toluenesulfonic acid, dodecylbenzenesulfonic acid, camphorsulfonic acid, naphthalenesulfonic acid, 2,4-dinitronaphthol-7-sulfonic acid, phosphate organic matter or benzoic acid and its derivatives.
[0017] In the present invention, the phosphate-based organic matter refers to an organic matter containing a phosphate group. Exemplarily, the phosphate-based organic matter includes at least one of n-butyl phosphate, ethyl phosphate, n-decyl phosphate or benzyl phosphate.
[0018] Preferably, the specific surface area of CeO2 is 195 to 215 m 2 / g, for example 195m 2 / g, 196m 2 / g, 197m 2 / g, 198m 2 / g, 199m 2 / g, 200m 2 / g, 201m 2 / g, 202m 2 / g, 203m 2 / g, 205m 2 / g, 210m 2 / g or 215m 2 / g.
[0019] The specific surface area of CeO2 in the present invention is preferably within the above range. A large specific surface area can increase the reaction activity of CeO2 and increase the sites for polymerization of polyaniline on the surface of CeO2, which is beneficial to the occurrence of the reaction.
[0020] Preferably, the pore size of the CeO2 is 30-50 nm, for example, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.
[0021] The pore size of CeO2 in the present invention is preferably within the above range. The relatively large pore size and regular pore structure can be used as a nanoreactor for polymerization reactions. Since the molecular weight distribution of polyaniline obtained by polymerization in the pores of the ordered mesoporous CeO2 material is narrower than that of the general polymerization method under corresponding conditions, the molecular weight of polyaniline can be controlled by changing the amount of aniline monomer and the reaction time, and active centers can be typed or introduced into the skeleton of the polymerization reactor to accelerate the reaction process.
[0022] Preferably, based on the mass of the positive electrode material as 100wt%, the content of the positive electrode active substance in the positive electrode material is 90.0-99.9wt%, for example, 90.0wt%, 91.0wt%, 92.0wt%, 93.0wt%, 94.0wt%, 95.0wt%, 96.0wt%, 97.0wt%, 98.0wt%, 99.0wt% or 99.9wt%.
[0023] Preferably, the chemical formula of the positive electrode active material includes Na x Ni y Fe z Mn b O2, wherein 1.3>x>0, x is, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or 1.3, 1>y>0, y is, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, 1>z>0, z is, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, 1>b>0, b is, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, y+z+b=1.
[0024] Preferably, 1.2≥x≥0.8, 0.5>y>0, 0.5>z>0, 0.8>b>0, y+z+b=1.
[0025] In one embodiment of the present invention, the Na x Ni y Fe z Mn b O2 is doped, and the doping element includes but is not limited to at least one of Li, Mg, Al, Ti, Zr, Ca, Cr, Sc, Sr, Y, W, Ce, Ta, Nb or In.
[0026] The present invention is to Na x Ni y Fe z Mn bThe source or preparation method of O2 is not limited. In one embodiment, the Na x Ni y Fe z Mn b O2 was prepared as follows:
[0027] Ni y Fe z Mn b (OH)2 is mixed and sintered with sodium salt, and then crushed and sieved to obtain the Na x Ni y Fe z Mn b O2.
[0028] In a second aspect, the present invention provides a method for preparing the positive electrode material as described in the first aspect, the method comprising the following steps:
[0029] (1) adding aniline, an oxidant and CeO2 into an acid to obtain a dispersion, and performing a polymerization reaction to obtain a polyaniline / CeO2 composite material;
[0030] (2) Dispersing the polyaniline / CeO2 composite material and the positive electrode active material in step (1) in a solvent, and drying to obtain the positive electrode material.
[0031] In the preparation process of the present invention, aniline undergoes polymerization reaction with CeO2 as a template to generate a polyaniline / CeO2 composite, and the polyaniline / CeO2 composite material improves the comprehensive conductivity (ionic conductivity and electronic conductivity) of the positive electrode material, stabilizes the structure of the polyaniline, and improves the thermal stability and rate performance of the positive electrode material; then, the polyaniline dispersed with CeO2 is relatively evenly coated on the surface of the positive electrode active material through the effect of electrostatic adsorption in a solvent, and a polyaniline coating layer is formed on the surface of the positive electrode active material, thereby preparing a positive electrode material with good rate performance and cycle performance.
[0032] Compared with the coating method of adding positive electrode active material during the polymerization process of aniline, the coating method of the present invention can prevent the residual alkali (NaOH, Na2CO3, LiOH or Li2CO3) on the surface of the positive electrode active material from undergoing acid-base neutralization reaction in an acidic medium, causing excessive erosion of the positive electrode active material, thereby causing damage to the surface structure of the positive electrode active material.
[0033] The present invention does not limit the preparation method of CeO2. For example, in one embodiment of the present invention, the preparation of CeO2 includes the following steps:
[0034] (1) dissolving cerium salt and cetyltrimethylammonium bromide (CTAB) in pure water at a molar ratio of 1:1;
[0035] (2) After stirring and dispersing, citric acid is added dropwise, wherein the molar ratio of citric acid to cerium salt is 1.2:1, and the solution gradually becomes viscous. After strong stirring, it is dried and calcined to prepare CeO2.
[0036] Preferably, the oxidant in step (1) includes at least one of (NH4)2S2O8, K2Cr2O7, KIO3, FeCl3, H2O2, Ce(SO4)2, MnO2 or benzoyl peroxide.
[0037] Preferably, the acid in step (1) is an organic protonic acid.
[0038] Organic protonic acid can not only serve as an acidic medium, but also be doped into the prepared polyaniline as a dopant, which can further enhance the electronic conductivity of polyaniline and improve the solubility of polyaniline.
[0039] Preferably, the organic protonic acid includes at least one of methanesulfonic acid, dodecylsulfonic acid, toluenesulfonic acid, dodecylbenzenesulfonic acid, camphorsulfonic acid, naphthalenesulfonic acid, 2,4-dinitronaphthol-7-sulfonic acid, phosphate organic matter or benzoic acid and its derivatives.
[0040] In the present invention, the phosphate-based organic matter refers to an organic matter containing a phosphate group. Exemplarily, the phosphate-based organic matter includes at least one of n-butyl phosphate, ethyl phosphate, n-decyl phosphate, benzyl phosphate, and the like.
[0041] Preferably, the molar ratio of aniline to oxidant in step (1) is (0.6-1):1, for example, "0.6-1" can be 0.6, 0.7, 0.8, 0.9 or 1.
[0042] Preferably, the mass ratio of aniline to CeO2 in step (1) is 1:(0.1-1.0), for example, "0.1-1.0" can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0.
[0043] In the present invention, when the CeO2 content is high, CeO2 will be surplus as a polymerization reaction template and cannot be fully dispersed in the polyaniline. Due to the low coating drying temperature, the surplus CeO2 will remain as an impurity on the surface of the positive electrode material, affecting the electrochemical properties of the material. When the CeO2 content is low, the polyaniline synthesized using CeO2 as a template has a low content, while the polyaniline without CeO2 is high, which cannot enhance the structural stability of the polyaniline, and thus cannot reflect the beneficial enhancement effect of the polyaniline / CeO2 composite material coating on the positive electrode material.
[0044] Preferably, the dispersion in step (1) is obtained according to the following steps:
[0045] a. Dissolve aniline and oxidant in acid respectively;
[0046] b. Adding an acid containing an oxidant and CeO2 to an acid containing aniline to obtain the dispersion.
[0047] The advantage of adopting the above steps is that the acid containing the oxidant and CeO2 are simultaneously introduced into the acid containing aniline, which is conducive to the polymerization reaction of aniline using CeO2 as a template and prevents the premature generation of polyaniline without CeO2 due to the late addition of CeO2.
[0048] Preferably, the reaction temperature in step (1) is -10 to 10°C, for example, -10°C, -9°C, -8°C, -7°C, -6°C, -5°C, -4°C, -3°C, -2°C, -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C or 10°C.
[0049] In the present invention, the lower reaction temperature is to prevent the polymerization rate of aniline from being too fast, thereby causing the phenomenon of uneven polyaniline coating.
[0050] Preferably, the reaction time of step (1) is 20 to 30 min, for example, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min.
[0051] The reaction time in the present invention is relatively short, which can improve the efficiency of the reaction on the one hand, and on the other hand, the molecular weight of the prepared polyaniline is relatively small, which is more conducive to the dissolution of the polyaniline in the solvent, so that the polyaniline is more evenly coated on the surface of the positive electrode active material through electrostatic adsorption. If the reaction time is relatively long, the molecular weight of the polyaniline will be relatively high, resulting in the thickness of the polyaniline coating layer on the surface of the positive electrode active material being too thick, making it difficult for ions to escape and embed, increasing the impedance of the positive electrode material, and reducing the capacity, first coulomb efficiency and rate performance of the positive electrode material.
[0052] Preferably, the polyaniline / CeO2 composite material in step (1) is washed and dried.
[0053] The present invention does not limit the solvent and number of washings. Exemplarily, the solvent includes but is not limited to at least one of water, ethanol or a mixture of water and ethanol, and the number of washings includes but is not limited to 1 time, 2 times or 3 times.
[0054] The present invention does not limit the drying temperature. Exemplarily, the drying temperature includes but is not limited to 60-100°C, such as 60°C, 70°C, 80°C, 90°C or 100°C.
[0055] The present invention does not limit the drying time. Exemplarily, the drying time includes but is not limited to 10 to 15 hours, such as 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours.
[0056] Preferably, in step (2), the mass ratio of the polyaniline / CeO2 composite material to the positive electrode active material is (0-0.1):1 and does not include 0:1, and “0-0.1” can be, for example, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1.
[0057] In the present invention, if the content of the polyaniline / CeO2 composite material is too low, the coating rate of the positive electrode material is too low, the coating effect cannot be achieved, and it is easy to react with the salt in the electrolyte, causing the dissolution of metal ions, reducing the rate and cycle performance of the material. If the content of the polyaniline / CeO2 composite material is high, the thickness of the polyaniline coating layer will be thicker, increasing the transmission distance of the ions, thereby affecting the ion extraction and embedding, increasing the impedance, and reducing the capacity and first coulomb efficiency of the material and the cycle performance.
[0058] Preferably, the solvent in step (2) comprises at least one of N-methylpyrrolidone or N,N-dimethylformamide.
[0059] Preferably, the dispersion temperature in step (2) is 30-60°C, for example, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C.
[0060] Preferably, the dispersion time in step (2) is 1 to 5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.
[0061] Preferably, the drying temperature in step (2) is 100-140°C, for example, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C.
[0062] Preferably, the drying time in step (2) is 10 to 20 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours or 20 hours.
[0063] In a third aspect, the present invention provides a battery, wherein the positive electrode of the battery comprises the positive electrode material described in the first aspect of the present invention.
[0064] The battery assembled using the positive electrode material described in the first aspect of the present invention has good cycle performance and good rate performance.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] (1) The surface of the positive electrode material in the present invention is coated with a polyaniline coating layer. On the one hand, the polyaniline coating layer can improve the stability of the positive electrode active material in the air. On the other hand, the polyaniline coating layer has good compatibility with the electrolyte and can avoid the contact between the electrolyte and the positive electrode active material, thereby inhibiting the side reaction between the electrolyte and the positive electrode active material. In addition, CeO2 is dispersed in the polyaniline, which increases the electronic conductivity and ionic conductivity of the positive electrode material and improves the comprehensive conductivity of the positive electrode material. CeO2 also enhances the structural stability of the polyaniline and the thermal stability of the positive electrode material. The above factors work together to improve the rate performance and cycle performance of the positive electrode material.
[0067] (2) The preparation method of the present invention is relatively simple. The polyaniline / CeO2 composite material is uniformly coated on the surface of the positive electrode active material through simple electrostatic adsorption. The cost is low and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 is a scanning electron microscope (SEM) image of the positive electrode material in Example 1 of the present invention;
[0069] Figure 2 This is a SEM image of the positive electrode material in Comparative Example 2 of the present invention;
[0070] Figure 3 This is a SEM image of the positive electrode material in Comparative Example 3 of the present invention;
[0071] Figure 4 The charge and discharge curves of CR2032 button cells assembled with the positive electrode materials in Example 1 and Comparative Examples 1 to 3 at a current density of 0.1C;
[0072] Figure 5 The capacity retention rate of CR2032 button cells assembled with the positive electrode materials in Example 1 and Comparative Examples 2-3 at a current density of 1C. DETAILED DESCRIPTION
[0073] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0074] Example 1
[0075] This embodiment provides a positive electrode material, the positive electrode material includes a positive electrode active material and a polyaniline coating layer located on the surface of the positive electrode active material, the polyaniline coating layer includes a polyaniline matrix and CeO2 dispersed in the polyaniline matrix. Based on the mass of the positive electrode material being 100wt%, the content of the polyaniline coating layer is 0.5wt%, and the content of the positive electrode active material is 99.5wt%; the molecular weight of the polyaniline in the polyaniline coating layer is 2500, the polyaniline is camphorsulfonic acid-doped polyaniline, and the specific surface area of the CeO2 is 205m 2 / g, and the pore size of the CeO2 is 45nm.
[0076] The preparation method of the positive electrode material is as follows:
[0077] 1. Preparation of primary sintering material:
[0078] Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and sodium carbonate are mixed in a high-speed mixer at a sodium to metal molar ratio of 1.02:1, and Li2CO3, TiO2 and SrCO3 are added, wherein the mass of Li2CO3 is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The mass of (OH)2 is 0.2wt%, the mass of TiO2 is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The mass of (OH)2 is 0.2wt%, the mass of SrCO3 is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The mixture is 0.2wt% of (OH)2 by weight, and then sintered at 1050°C for 10h in an air atmosphere, cooled naturally in the furnace, and then crushed and sieved to obtain a primary sintering material;
[0079] 2. Preparation of camphorsulfonic acid doped polyaniline / CeO2 composite materials:
[0080] (1) Cerium nitrate and CTAB were dissolved in pure water at a molar ratio of 1:1, stirred for 5 minutes to make them evenly dispersed, and then citric acid (the molar ratio of citric acid to cerium nitrate was 1.2:1) was added dropwise, and the solution gradually became viscous. After strong stirring for 3 hours, the gel was dried by air blast, and the dried gel solid was calcined at 300°C for 6 hours to obtain CeO2 powder;
[0081] (2) dissolving aniline (C6H5NH2) and (NH4)2S2O8 in a molar ratio of 0.8:1 in camphorsulfonic acid at a concentration of 1 mol / L, and then simultaneously and rapidly introducing the (NH4)2S2O8 solution and CeO2 powder into the acidified aniline solution (wherein the mass ratio of aniline to CeO2 powder is 1:0.42) to obtain a dispersion;
[0082] (3) stirring the dispersion in step (2) at 0° C. for 20 min, reacting until a precipitate appears, filtering the precipitate, washing it with distilled water and ethanol three times each, and drying the obtained solid at 80° C. for 12 h to obtain a camphorsulfonic acid-doped polyaniline / CeO2 composite material;
[0083] 3. Preparation of positive electrode materials coated with camphorsulfonic acid-doped polyaniline / CeO2 composite materials:
[0084] The camphorsulfonic acid-doped polyaniline / CeO2 composite material of step 2 is placed in a solvent N-methylpyrrolidone (NMP) and ultrasonically stirred. After it is dispersed and dissolved, the primary sintered material obtained in step 1 is added, wherein the mass of the camphorsulfonic acid-doped polyaniline / CeO2 composite material is 0.5wt% of the mass of the primary sintered material. The mixture is dispersed in a water bath at 45°C and maintained for 3 hours. Then, the suspension is filtered to obtain a solid, which is placed in a vacuum drying oven at 120°C and vacuum dried for 12 hours to obtain a positive electrode material coated with the camphorsulfonic acid-doped polyaniline / CeO2 composite material.
[0085] Example 2
[0086] This embodiment provides a positive electrode material, the positive electrode material includes a positive electrode active material and a polyaniline coating layer located on the surface of the positive electrode active material, the polyaniline coating layer includes CeO2 dispersed therein. Based on the mass of the positive electrode material being 100wt%, the content of the polyaniline coating layer is 1.0wt%, and the content of the positive electrode active material is 99.0wt%; the molecular weight of the polyaniline in the polyaniline coating layer is 4500, the polyaniline is methanesulfonic acid-doped polyaniline, and the specific surface area of the CeO2 is 211m 2 / g, and the pore size of the CeO2 is 32nm.
[0087] The preparation method of the positive electrode material is as follows:
[0088] 1. Preparation of primary sintering material:
[0089] Ni 0.25 Fe 0.5 Mn 0.25 (OH)2 and sodium carbonate are mixed in a high-speed mixer at a sodium to metal molar ratio of 1.02:1, and MgO and ZrO2 are added, wherein the mass of MgO is Ni0.25 Fe 0.5 Mn 0.25 The mass of (OH)2 is 0.5wt%, the mass of ZrO2 is Ni 0.25 Fe 0.5 Mn 0.25 The mixture is 0.2wt% of (OH)2 by weight, and then sintered at 1050°C for 10h in an air atmosphere, cooled naturally in the furnace, and then crushed and sieved to obtain a primary sintering material;
[0090] 2. Preparation of methanesulfonic acid doped polyaniline / CeO2 composite materials:
[0091] (1) Cerium nitrate and CTAB were dissolved in pure water at a molar ratio of 1:1, stirred for 5 minutes to make them evenly dispersed, and then citric acid (the molar ratio of citric acid to cerium nitrate was 1.2:1) was added dropwise, and the solution gradually became viscous. After strong stirring for 3 hours, the gel was dried by air blast, and the dried gel solid was calcined at 300°C for 6 hours to obtain CeO2 powder;
[0092] (2) C6H5NH2 and FeCl3 were dissolved in 1 mol / L methanesulfonic acid at a molar ratio of 1:1, and then the FeCl3 solution and CeO2 powder were simultaneously and rapidly introduced into an acidified aniline solution (wherein the mass ratio of aniline to CeO2 powder was 1:0.3) to obtain a dispersion;
[0093] (3) stirring the dispersion in step (2) at -5°C for 25 min to react until precipitation occurs, filtering the precipitate, washing it with distilled water and ethanol three times each, and drying the obtained solid at 80°C for 12 h to obtain a methanesulfonic acid-doped polyaniline / CeO2 composite material;
[0094] 3. Preparation of positive electrode materials coated with methanesulfonic acid-doped polyaniline / CeO2 composite materials:
[0095] The methanesulfonic acid-doped polyaniline / CeO2 composite material of step 2 is placed in a solvent NMP and ultrasonically stirred. After it is dispersed and dissolved, the primary sintered material obtained in step 1 is added, wherein the mass of the methanesulfonic acid-doped polyaniline / CeO2 composite material is 3wt% of the mass of the primary sintered material. The composite material is dispersed in a water bath at 60°C and maintained for 4 hours. Then the suspension is filtered to obtain a solid, which is placed in a vacuum drying oven at 100°C and vacuum dried for 15 hours to obtain a positive electrode material coated with the methanesulfonic acid-doped polyaniline / CeO2 composite material.
[0096] Example 3
[0097] This embodiment provides a positive electrode material, which includes a positive electrode active material and a polyaniline coating layer located on the surface of the positive electrode active material, wherein the polyaniline coating layer includes CeO2 dispersed therein. Based on the mass of the positive electrode material being 100wt%, the content of the polyaniline coating layer is 1.5wt%, and the content of the positive electrode active material is 98.5wt%; the molecular weight of the polyaniline in the polyaniline coating layer is 8000, the polyaniline is doped with dodecylbenzenesulfonic acid, and the specific surface area of the CeO2 is 197m 2 / g, and the pore size of the CeO2 is 49nm.
[0098] The preparation method of the positive electrode material is as follows:
[0099] 1. Preparation of primary sintering material:
[0100] Ni 0.2 Fe 0.5 Mn 0.3 (OH)2 and sodium carbonate are mixed in a high-speed mixer at a sodium to metal molar ratio of 1.02:1, and then sintered at 1050°C for 10 hours in an air atmosphere, cooled naturally in the furnace, and crushed and sieved to obtain a primary sintering material;
[0101] 2. Preparation of positive electrode material coated with dodecylbenzenesulfonic acid-doped polyaniline / CeO2 composite material:
[0102] (1) Cerium nitrate and CTAB were dissolved in pure water at a molar ratio of 1:1, stirred for 5 minutes to make them evenly dispersed, and then citric acid (the molar ratio of citric acid to cerium nitrate was 1.2:1) was added dropwise, and the solution gradually became viscous. After strong stirring for 3 hours, the gel was dried by air blast, and the dried gel solid was calcined at 300°C for 6 hours to obtain CeO2 powder;
[0103] (2) C6H5NH2 and H2O2 were dissolved in 1 mol / L dodecylbenzenesulfonic acid at a molar ratio of 0.6:1, and then the H2O2 solution and CeO2 powder were simultaneously and rapidly introduced into an acidified aniline solution (wherein the mass ratio of aniline to CeO2 powder was 1:0.5) to obtain a dispersion;
[0104] (3) stirring the dispersion in step (2) at 5° C. for 30 min to react until a precipitate appears, filtering the precipitate, washing it with distilled water and ethanol three times each, and drying the obtained solid at 80° C. for 12 h to obtain a dodecylbenzenesulfonic acid-doped polyaniline / CeO2 composite material;
[0105] 3. Preparation of positive electrode material coated with dodecylbenzenesulfonic acid doped polyaniline / CeO2 composite material:
[0106] The dodecylbenzenesulfonic acid-doped polyaniline / CeO2 composite material of step 2 is placed in a solvent NMP and ultrasonically stirred. After it is dispersed and dissolved, the primary sintering material obtained in step 1 is added, wherein the mass of the dodecylbenzenesulfonic acid-doped polyaniline / CeO2 composite material is 6wt% of the mass of the primary sintering material. The composite material is dispersed in a water bath at 30°C and maintained for 5h. Then the suspension is filtered to obtain a solid, which is placed in a vacuum drying oven at 140°C and vacuum dried for 18h to obtain a positive electrode material coated with the dodecylbenzenesulfonic acid-doped polyaniline / CeO2 composite material.
[0107] Example 4
[0108] Compared with Example 1, the only difference is that hydrochloric acid is used instead of camphorsulfonic acid in step 2.
[0109] Example 5
[0110] Compared with Example 1, the only difference is that in the process of preparing the camphorsulfonic acid-doped polyaniline / CeO2 composite material in step 2, the mass ratio of aniline to CeO2 is 1:0.6.
[0111] Example 6
[0112] Compared with Example 1, the only difference is that in the process of preparing the camphorsulfonic acid-doped polyaniline / CeO2 composite material in step 2, the mass ratio of aniline to CeO2 is 1:0.2.
[0113] Example 7
[0114] Compared with Example 1, the only difference is that in the process of preparing the camphorsulfonic acid-doped polyaniline / CeO2 composite material in step 2, the reaction time of the dispersion is extended from 20 min to 50 min.
[0115] Example 8
[0116] Compared with Example 1, the only difference is that in the process of preparing the positive electrode material coated with the camphorsulfonic acid-doped polyaniline / CeO2 composite material in step 3, the mass ratio of the camphorsulfonic acid-doped polyaniline / CeO2 composite material to the positive electrode active material is 0.15:1.
[0117] Comparative Example 1
[0118] This comparative example provides a method for preparing a positive electrode material, comprising:
[0119] Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and sodium carbonate are mixed in a high-speed mixer at a sodium to metal molar ratio of 1.02:1, and Li2CO3, TiO2 and SrCO3 are added, wherein the mass of Li2CO3 is Ni 1 / 3 Fe1 / 3 Mn 1 / 3 The mass of (OH)2 is 0.2wt%, the mass of TiO2 is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The mass of (OH)2 is 0.2wt%, the mass of SrCO3 is Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The mixture is added with 0.2 wt% of (OH)2 by mass, and then sintered at 1050°C for 10 h in an air atmosphere, cooled naturally in the furnace, and a primary sintered material is prepared after crushing and sieving, which is the positive electrode material in Comparative Example 1.
[0120] Comparative Example 2
[0121] This comparative example provides a method for preparing a positive electrode material, comprising:
[0122] 1. Preparation of primary sintering material:
[0123] The preparation steps of the primary sintering material are the same as those in Example 1;
[0124] 2. Preparation of B-coated positive electrode material:
[0125] The primary sintered material in step 1 is mixed with boric acid, wherein the mass of the boric acid is 0.2wt% of the mass of the primary sintered material, and then sintered at 250°C for 6h in an air atmosphere, cooled naturally in the furnace, and then crushed and sieved to obtain a B-coated positive electrode material.
[0126] Comparative Example 3
[0127] The only difference compared with Example 1 is that in step 2, CeO2 powder is not prepared and added.
[0128] Comparative Example 4
[0129] 1. Preparation of primary sintering material:
[0130] The preparation steps of the primary sintering material are the same as those in Example 1;
[0131] 2. Preparation of camphorsulfonic acid-doped polyaniline:
[0132] C6H5NH2 and (NH4)2S2O8 are dissolved in camphorsulfonic acid with a concentration of 1 mol / L in a molar ratio of 0.8:1, and then the (NH4)2S2O8 solution is quickly introduced into an acidified aniline solution to obtain a dispersion; the dispersion is stirred at 0°C for 20 minutes, reacted until a precipitate appears, and then the precipitate is filtered, washed with distilled water and ethanol for 3 times each, and the obtained solid is dried at 80°C for 12 hours to obtain camphorsulfonic acid-doped polyaniline;
[0133] 3. Preparation of camphorsulfonic acid-doped polyaniline-coated positive electrode material:
[0134] The camphorsulfonic acid-doped polyaniline in step 2 is placed in a solvent NMP and ultrasonically stirred, and after it is dispersed and dissolved, the primary sintering material obtained in step 1 is added, wherein the mass of the camphorsulfonic acid-doped polyaniline is 0.5wt% of the mass of the primary sintering material, and the dispersion is carried out in a water bath at 45° C. and maintained for 3 hours, and then the suspension is filtered to obtain a solid, which is placed in a vacuum drying oven at 120° C. and vacuum dried for 12 hours to obtain a positive electrode material coated with camphorsulfonic acid-doped polyaniline;
[0135] 4. Preparation of positive electrode materials coated with cerium dioxide and camphorsulfonic acid doped polyaniline:
[0136] Dissolve cerium nitrate with deionized water, then add the camphorsulfonic acid-doped polyaniline-coated positive electrode material in step 3, mix and stir at 100°C until the solution evaporates, and then dry at 80°C for 5 hours. The obtained powder is placed in a tubular furnace and calcined at 800°C for 6 hours to obtain a cerium dioxide and camphorsulfonic acid-doped polyaniline-coated positive electrode material.
[0137] Comparative Example 5
[0138] Compared with Example 1, the only difference is that a positive electrode active material is added during the preparation of the camphorsulfonic acid-doped polyaniline / CeO2 composite material.
[0139] The positive electrode materials in Example 1 and Comparative Examples 2-3 were subjected to SEM testing, and the test results are as follows: Figures 1 to 3 As shown, Figure 1 This is the SEM test result of the positive electrode material in Example 1. Figure 2 This is the SEM test result of the positive electrode material in Comparative Example 2. Figure 3 The SEM test results of the positive electrode material in Comparative Example 3 are as follows: Figures 1 to 3 It can be seen that there are no obvious agglomerated particles on the surface of the positive electrode material in Example 1 of the present invention, indicating that the coating layer of the positive electrode material in Example 1 of the present invention has an appropriate thickness and is relatively uniformly coated.
[0140] Performance testing:
[0141] The CR2032 button cells assembled with the positive electrode materials in Examples 1 to 8 and Comparative Examples 1 to 5 were subjected to electrical performance tests on a blue-electric test system.
[0142] 1. CR2032 button battery
[0143] (1) Positive electrode sheet: Positive electrode material: polyvinylidene fluoride: Supper P = 95:2.5:2.5;
[0144] (2) Counter electrode: metal sodium sheet;
[0145] (3) Diaphragm: glass fiber;
[0146] (4) Electrolyte: The solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1, and the sodium salt is 1 mol / L NaPF6.
[0147] 2. Test conditions
[0148] The test temperature was 25°C, the test voltage range was 2.0-4.0V, 0.1C cycle for 1 week, 0.2C cycle for 1 week, 0.5C cycle for 1 week, and 1C cycle for 50 weeks.
[0149] The first week charge and discharge curves of the CR2032 button cells assembled with the positive electrode materials in Example 1 and Comparative Examples 1 to 3 at a current density of 0.1C are as follows: Figure 4 As shown, from Figure 4 It can be seen that the CR2032 button cell assembled with the positive electrode material in Example 1 of the present invention has a higher discharge specific capacity at a current density of 0.1C.
[0150] The capacity retention rate of the CR2032 button cell assembled with the positive electrode materials in Example 1 and Comparative Examples 2 to 3 at a current density of 1C is as follows: Figure 5 As shown, from Figure 5 It can be seen that the capacity retention rate of the CR2032 button battery assembled with the positive electrode material in Example 1 of the present invention is relatively high.
[0151] The discharge specific capacity of the CR2032 button-type batteries assembled with the positive electrode materials in Examples 1 to 8 and Comparative Examples 1 to 5 at a current density of 0.1C and the capacity retention rate at a current density of 1C are shown in Table 1:
[0152] Table 1
[0153]
[0154]
[0155] The discharge specific capacities of CR2032 button cells assembled with the positive electrode materials in Examples 1 to 8 and Comparative Examples 1 to 5 at different current densities are shown in Table 2.
[0156] Table 2
[0157]
[0158] analyze:
[0159] It can be seen from the data in the examples that the battery assembled with the positive electrode material in the examples of the present invention has good cycle performance and rate performance, indicating that the modification of the positive electrode material in the present invention is an effective method to improve the electrochemical performance of the positive electrode material.
[0160] It can be seen from the data of Example 1 and Example 4 that doping polyaniline with an organic protonic acid can further improve the performance of polyaniline, thereby further improving the electrochemical performance of the prepared positive electrode material.
[0161] It can be seen from the data of Examples 1 and 5 to 6 that the content of CeO2 dispersed in the polyaniline coating layer of the present invention has a great influence on the cycle performance and rate performance of the prepared positive electrode material, and excessive or insufficient CeO2 content will affect the electrochemical properties of the prepared positive electrode material.
[0162] It can be seen from the data of Example 1 and Example 7 that the reaction time of the dispersion formed by aniline, oxidant and CeO2 powder has an important influence on the electrochemical properties of the positive electrode material. The reaction time should not be too long. If the reaction time process will cause the molecular weight of polyaniline to be too large, the thickness of the coating layer on the surface of the positive electrode active material will be thicker, affecting the cycle performance and rate performance of the positive electrode material.
[0163] It can be seen from the data of Example 1 and Example 8 that the thickness of the coating layer has an influence on the cycle performance and rate performance of the prepared positive electrode material. If the thickness of the coating layer is too thick, the electrochemical performance of the positive electrode material will be affected.
[0164] It can be seen from the data of Example 1 and Comparative Examples 1 to 2 that, compared with the unmodified positive electrode material, the method for modifying the positive electrode material in the present invention can improve the cycle performance and rate performance of the positive electrode material, and the method for modifying the positive electrode material in the present invention is superior to the modification of the positive electrode active material by the B coating layer in the prior art.
[0165] It can be seen from the data in Example 1 and Comparative Example 3 that CeO2 has an influence on the electrochemical properties of the positive electrode material in the present invention. When CeO2 is not dispersed in the polyaniline coating layer, it will have an adverse effect on the electrochemical properties of the positive electrode material.
[0166] It can be seen from the data of Example 1 and Comparative Example 4 that, compared with coating CeO2 on the surface of the positive electrode material, the method of dispersing CeO2 in the polyaniline coating layer in the present invention can better improve the electrochemical performance of the positive electrode material.
[0167] It can be seen from the data of Example 1 and Comparative Example 5 that in the modification process of the positive electrode material of the present invention, the order of adding the positive electrode active substance has a great influence on the performance of the positive electrode material. When the positive electrode active substance is added during the preparation process of the camphorsulfonic acid-doped polyaniline / CeO2 composite material, the residual alkali on the surface of the positive electrode active substance will react with the camphorsulfonic acid, thereby corroding the positive electrode active substance, and further adversely affecting the electrochemical properties of the positive electrode material.
[0168] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a positive electrode active material and a polyaniline coating layer located on the surface of the positive electrode active material, wherein the polyaniline coating layer comprises a polyaniline matrix and ordered mesoporous CeO2 dispersed in the polyaniline matrix; The chemical formula of the positive electrode active material includes Na x Ni y Fe z Mn b O2, among which, 1.3>x>0, 1>y>0, 1>z>0, 1>b>0, y+z+b=1; The polyaniline in the polyaniline coating layer is organic protonic acid-doped polyaniline; The organic protonic acid includes at least one of methanesulfonic acid, dodecylsulfonic acid, toluenesulfonic acid, dodecylbenzenesulfonic acid, camphorsulfonic acid, naphthalenesulfonic acid or 2,4-dinitronapthol-7-sulfonic acid; The positive electrode material is prepared by the following method: (1) adding aniline, an oxidant and ordered mesoporous CeO2 into an acid to obtain a dispersion, and performing a polymerization reaction to obtain a polyaniline / ordered mesoporous CeO2 composite material; (2) dispersing the polyaniline / ordered mesoporous CeO2 composite material and the positive electrode active material in step (1) in a solvent, and drying to obtain the positive electrode material; The acid in step (1) is an organic protonic acid.
2. The positive electrode material according to claim 1, characterized in that Based on 100wt% of the mass of the positive electrode material, the content of the polyaniline coating layer is 0.1-10wt%.
3. The positive electrode material according to claim 1, characterized in that The molecular weight of the polyaniline in the polyaniline coating layer is 1000-10000.
4. The positive electrode material according to claim 1, characterized in that The specific surface area of the ordered mesoporous CeO2 is 195~215m 2 / g.
5. The positive electrode material according to claim 1, characterized in that The average pore size of the ordered mesoporous CeO2 is 30-50 nm.
6. The positive electrode material according to claim 1, characterized in that Taking the mass of the positive electrode material as 100wt%, the content of the positive electrode active material in the positive electrode material is 90.0-99.9wt%.
7. The positive electrode material according to claim 1, characterized in that 1.2≥x≥0.8, 0.5>y>0, 0.5>z>0, 0.8>b>0, y+z+b=1.
8. A method for preparing the positive electrode material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: (1) adding aniline, an oxidant and ordered mesoporous CeO2 into an acid to obtain a dispersion, and performing a polymerization reaction to obtain a polyaniline / CeO2 composite material; (2) dispersing the polyaniline / ordered mesoporous CeO2 composite material and the positive electrode active material in step (1) in a solvent, and drying to obtain the positive electrode material; The acid in step (1) is an organic protonic acid; The organic protonic acid includes at least one of methanesulfonic acid, dodecylsulfonic acid, toluenesulfonic acid, dodecylbenzenesulfonic acid, camphorsulfonic acid, naphthalenesulfonic acid or 2,4-dinitronapthol-7-sulfonic acid.
9. The preparation method according to claim 8, characterized in that: The oxidant in step (1) includes at least one of (NH4)2S2O8, K2Cr2O7, KIO3, FeCl3, H2O2, Ce(SO4)2, MnO2 or benzoyl peroxide.
10. The preparation method according to claim 8, characterized in that: The molar ratio of aniline to oxidant in step (1) is (0.6-1):
1.
11. The preparation method according to claim 8, characterized in that: The mass ratio of aniline to ordered mesoporous CeO2 in step (1) is 1:(0.1~1.0).
12. The preparation method according to claim 8, characterized in that: The dispersion in step (1) is obtained by the following steps: a. Dissolve aniline and oxidant in acid respectively; b. Adding an acid containing an oxidant and ordered mesoporous CeO2 to an acid containing aniline to obtain a mixed dispersion.
13. The preparation method according to claim 8, characterized in that: The reaction temperature in step (1) is -10~10°C.
14. The preparation method according to claim 8, characterized in that: The reaction time of step (1) is 20 to 30 minutes.
15. The preparation method according to claim 8, characterized in that: The polyaniline / CeO2 composite material in step (1) is washed and dried.
16. The preparation method according to claim 8, characterized in that: In step (2), the mass ratio of the polyaniline / ordered mesoporous CeO2 composite material to the positive electrode active material is (0-0.1):1 and does not include 0:
1.
17. The preparation method according to claim 8, characterized in that: The solvent in step (2) includes at least one of N-methylpyrrolidone and N,N-dimethylformamide.
18. The preparation method according to claim 8, characterized in that: The dispersion temperature in step (2) is 30-60°C.
19. The preparation method according to claim 8, characterized in that: The dispersion time in step (2) is 1 to 5 hours.
20. The preparation method according to claim 8, characterized in that: The drying temperature in step (2) is 100-140°C.
21. The preparation method according to claim 8, characterized in that: The drying time in step (2) is 10 to 20 hours.
22. A battery, characterized in that: The positive electrode of the battery comprises the positive electrode material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Olivine NaMPO4 coated high-nickel ternary or lithium-rich manganese-based positive electrode material and preparation method thereof
CN115148970A
Element-doped and cobalt in-situ coated precursor material, preparation method thereof and positive electrode material
CN115159593A
Coated sodium ion battery positive electrode material
CN115207325A
Carbon nanotube array / polyaniline / ceria composite material electrode, preparation method and application of carbon nanotube array / polyaniline / ceria composite material electrode
CN106548877A
Polyaniline coated ternary positive electrode material, preparation method, battery positive electrode and lithium battery thereof
CN108172759A